Differential expression of serum proteins before 20 weeks gestation in women with hypertensive disorders of pregnancy: A potential role for SH3BGRL3. (15th January 2021) - Jiang, Min; Lash, Gendie E.; Zeng, Shanshui; Liu, Fei; Han, Mengru; Long, Yan; Cai, Minmin; Hou, Huomei; Ning, Feng; Hu, Yanwei; Yang, Hongling
Abstract: Introduction: The objective of this study was to explore serum levels of differentially abundant proteins between women with hypertensive disorders of pregnancy (HDP) and women with normal-term pregnancy, and to explore the contribution of SH3BGRL3 to the pathogenesis of HDP. Methods: At 6–20 weeks gestation 48 pregnant women who later developed HDP (HDP group) and 48 women with normal-term pregnancy (normal group) were recruited based on maternal age and gestational age at a 1:1 ratio. Total serum protein was extracted, denatured, deoxidized, and subjected to enzymolysis. The sample was labeled with Tandem Mass Tags and analyzed via mass spectroscopy to identify differentially abundant proteins. The role of SH3BGRL3 in trophoblast invasion, proliferation and apoptosis was examined using the HTR-8/SVneo cell line and primary isolates of extravillous trophoblast (EVT) cells. Results: In the proteomic profiling analysis, there were 19 proteins that showed significant differential abundance (P < 0.05). Among them, 13 proteins were more abundant and 6 proteins were less abundant in the serum from the HDP group compared with the normal group. The function of one of the more abundant proteins, SH3BGRL3, in trophoblast cell invasion, proliferation and apoptosis was investigated. Treatment of the EVT cells or the HTR-8/SVneo cell line with anti-SH3BGRL3 inhibited proliferation, but stimulated both apoptosis and invasion. MMP2 and p-ERK levels were also decreased in EVT after anti-SH3BGRL3 treatment. Discussion: The SH3BGRL3 protein can regulate various aspects of trophoblast biology, and may be useful in the clinical diagnosis of HDP. Highlights: 19 proteins were differentially expressed between HDP and control patients before 20 weeks gestation. SH3BGRL3 inhibits invasion of EVT cells. SH3BGRL3 effects may be mediated by pERK signalling.